Identidade nacional e literatura indianista: discursos para a construção de uma identidade nacional brasileira em Gonçalves Dias - AZEVEDO, Philipe Luiz Trindade de (2020)
Literature in the 19th century was used as a strategy for building a national identification. Indianist literature sought to meet the interest of homogenizing a heterogeneous population. The present thesis, taking Indianist literature as an empirical field of study, analyzes the discourse present in the work of Gonçalves Dias focused on the construction of a national identity. In this sense, it seeks to correlate the life trajectory of Gonçalves Dias to the themes addressed by his oeuvre in prose and poetry, in order to understand his perspectives regarding the construction of the Indian as an element of national identification. It starts from the assumption, based on Bourdieu (2008), that language is not just a communication system, but the use of language refers to the establishment of a power dynamic necessary for the establishment of norms, customs, and institutions. In this sense, supported by Anderson (2008) and Guibernau (1997), he considers that the strengthening of a national identity requires not only political interventions, but a possible imposition by the state power, and it is also important to note that the sentimental appeal is also necessary for the identification between a people and their nation. These identifications could be constructed in different ways, for example, through the improvement of the educational system, the circulation of journals in vernacular languages, the institution of ephemeris, etc. The present thesis works from the perspective of building nationality through literature.